RBAC Standard Rationale Comments on "A Critique of the ANSI Standard on Role-Based Access Control". - Ferraiolo, D.
"For original paper see Ninghui Li et al., vol. 5, no. 6, p.41, (2007)". Some notion of roles for access control predates the research papers cited by the authors by at least a decade. Our work was designed to formalize RBAC and add features (such as hierarchies and constraints) to make it more useful to software developers and administrators. Extensive discussion of these and subsequent papers over many years led to the consensus standard for RBAC.
Keywords: ANSI standard; RBAC standard; Role-based access control standard; Software developer